Local Wisdom-Based Women's Empowerment: Study of Rattan Weaving Craftsmen in the Betang Asi Credit Union Cooperative Business Group in Pulang Pisau Regency, Central Kalimantan Province - Rita Sarlawa; Saputra Adiwijaya (Budapest International Research and Critics University, 2019)
The independence of society is inseparable from the emergence of the independence of individuals who are in it, including women. Women who are members of the Betang Asi Credit Union Cooperative business unit in Pulang Pisau Regency, Central Kalimantan Province with their efforts to wick rattan provide a new meaning in empowering women based on local wisdom of Dayak tribe, with a focus on business based on the potential of rattan plants that grow in nature. This research uses a descriptive qualitative method with a case study approach. The results of this study provide a review of the need for women to join business institutions such as cooperatives or other institutions in marketing their products, so that the weaknesses of the findings in this study can be eliminated and the role of women in the village towards economic independence can run well without having to forget the local wisdom as a person born from Dayak tribe.